2019
DOI: 10.1155/2019/2486216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Calibration Method for Field Application of UAV‐Based Soil Water Content Prediction Equation

Abstract: The objective of this study is to monitor the water content of soil quickly and accurately using a UAV. Because UAVs have higher spatial and temporal resolution than satellites, they are currently becoming more useful in remote sensing areas. We developed a water content estimation equation using the color of the soil and suggested a calibration method for field application. Since the resolution of the images taken by the UAV is different according to the altitude, the water content estimation formula is devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…• Irrigation management: UAVs assist in obtaining critical irrigation data at any time and at a low cost (Kim et al 2019).…”
Section: Grammatikis Et Al 2020)mentioning
confidence: 99%
“…• Irrigation management: UAVs assist in obtaining critical irrigation data at any time and at a low cost (Kim et al 2019).…”
Section: Grammatikis Et Al 2020)mentioning
confidence: 99%
“…Digital image analysis is fast, inexpensive, and repeatable and has a wide range of applications [13][14][15][16][17]. As regards soils, digital image analysis is also being used to predict various soil properties such as water content [12,[18][19][20], density [12,20], soil cracks [21,22], permeability [23,24], settling velocity [25,26] and strength [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing upon the principle of the remote sensing technique, the image-based methods have been proposed and increasingly applied to measure soil moisture content [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].The image-based technique commonly employs an ordinary digital camera to capture soil sample, and the moisture content is derived from soil color using the pre-established calibration curve. It is obvious that the calibration relationship between soil moisture content and its color is the key for employing the image-based technique.…”
Section: Introductionmentioning
confidence: 99%
“…Rahimi-Ajdadi et al [ 30 ] developed a machine vision model for predicting the soil moisture using image analysis; this model enables an estimate of soil moisture by only using three color features, including the mode of the color channel of blue and means of the color channels of normalized red and blue. Kim et al [ 31 ] developed a water content estimation equation using soil color and suggested a calibration method for field application of this equation to predict soil water content with unmanned aerial vehicle (UAV) images. Besides, Kirillova et al [ 32 ] investigated calibration methods for measuring the color of moist soils with digital cameras and showed that a decrease in soil moisture leads to a significant increase in lightness and yellowness.…”
Section: Introductionmentioning
confidence: 99%